Draft for discussion. Supporting women farmers in a changing climate: five policy lessons - Huyer, Sophia; Twyman, Jennifer; Koningstein, Manon; Ashby, Jacqueline A.; Vermeulen, Sonja J. (2015)
Climate change demands new approaches to agriculture: farmers’ practices will need to change in order to adapt to and mitigate changing conditions. This is also a gender issue: in the least developed countries 79% of economically active women report agriculture as their primary economic activity (FAOSTAT, cited in Doss 2011). Agriculture is a fundamental part of women’s livelihoods, especially in least developed countries and more women are moving into agriculture as men move out to seasonal or paid labour elsewhere. At the same time we know that women farmers have less access to productive inputs and resources for farming across the globe – FAO etc. Policies and practices to help farmers develop new approaches to combat climate change will need to recognize these demographic changes, and produce results for women farmers as well as men. This brief provides five policy lessons to support this process.